Visitor Emotional Solidarity and Planned Behavior Effects on Leisure and Tourism Development in Ghana - Asimah, Vincent Kweku; Hurriyati, Ratih; Gaffar, Vanessa; Wibowo, Lili Adi (Universitas Pendidikan Indonesia, 2023)
The study seeks to develop a relationship between Emotional Solidarity (ES) and the Theory of Planned Behavior (TPB) in predicting visitors’ behavioral intentions to attend leisure events in Ghana. ES Scale (ESS) modified with Tourism Impact Attitude Scale was employed. The data used IBM SPSS 25.0 and SmartPLS 3.3.9 for analysis. The hypotheses were explored using PLS-SEM. ES factors significantly positively affect visitors’ attitudes towards tourism development. The TPB significantly predicted the behavioral intentions of leisure event visitors. The study specifically suggests the promotion of tourism development with high perceived behavioral control, individual attitude, and subjective norms.